2018
DOI: 10.3390/medicines5030071
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Cholinesterase and Antioxidant Activity of Extracts of Moringa oleifera Plants from Rivers State, Niger Delta, Nigeria

Abstract: This study evaluated Moringa oleifera extracts from two locations in Niger Delta for in vitro anti-cholinesterase and antioxidant activities. Methanolic, aqueous and ethanolic extracts of Moringa oleifera were evaluated for inhibition of acetylcholinesterase (AChE) activity, antioxidant properties, and total phenolic and flavonoid contents using standard procedures. M. oleifera extracts possessed significant and concentration dependent AChE inhibitory activity for methanolic, aqueous, and ethanolic extracts. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 69 publications
3
19
0
1
Order By: Relevance
“…Likewise, the amount of total flavonoids among the aqueous and ethanol extract of dried leaves of M.oleifera, the ethanol based extract revealed the maximum amount of total flavonoids (6.20 g isoquercetin equivalents/100 g extract) 44 . Our result was in close agreement with this findings revealed that leaves of M.oleifera for total flavonoids of 61.618 mg/gm of dry 3) and ethanolic leaf (69.7 -342.5) extract revealed significant amount of total flavonoids than the aqueous extract (27.0-87.2 mg QUER E/g) 45 . Sulaiman Mohammed and Fazilah Abd Manan (2015) revealed the total flavonoid content from the seeds of moringa was 2.900 ± 0.0002 (mg Quercetin equivalents /g dry matter) 46 which was very similar to our results.…”
Section: Estimation Of Total Flavonoids (Antioxidants)supporting
confidence: 93%
“…Likewise, the amount of total flavonoids among the aqueous and ethanol extract of dried leaves of M.oleifera, the ethanol based extract revealed the maximum amount of total flavonoids (6.20 g isoquercetin equivalents/100 g extract) 44 . Our result was in close agreement with this findings revealed that leaves of M.oleifera for total flavonoids of 61.618 mg/gm of dry 3) and ethanolic leaf (69.7 -342.5) extract revealed significant amount of total flavonoids than the aqueous extract (27.0-87.2 mg QUER E/g) 45 . Sulaiman Mohammed and Fazilah Abd Manan (2015) revealed the total flavonoid content from the seeds of moringa was 2.900 ± 0.0002 (mg Quercetin equivalents /g dry matter) 46 which was very similar to our results.…”
Section: Estimation Of Total Flavonoids (Antioxidants)supporting
confidence: 93%
“…Compared with this study, the seeds from both Kenya and Nigeria had the lowest TFC, while the TFC of leaves was higher than roots in Kenya and the opposite occurred in Nigeria. The differences may be caused by the differences in climate and soil compositions of the different growing areas [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…Among the analyzed samples, four of them (samples 5, 10, 11 and 13) have got the lowest values of AChE inhibitory activity. This could be explained by a lower content of polyphenolic compounds [36,37] and lower antioxidant activity among the analyzed water extracts [38]. The standards (gallic acid, caffeic acid, rutin, and ascorbic acid) also did not show any significant AChE inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%